Differences between novel hybrid mode flaps and traditional perforator flaps at the level of metabolites using LC–MS. (30th August 2022) - Li, Shi; Luo, Xiaobin; Zhang, Zhe; Raza, Mazhar Ali; Jin, Zeyuan; Yao, Chenglun; Yan, Hede
Abstract: The multi‐territory perforator flaps are widely used in plastic surgery. However, partial necrosis flap in the potential territory remains a challenge to plastic surgeons. We raised a novel "hybrid nourished mode" (HNM) flap based on the multi‐territory deep inferior epigastric perforator (DIEP) flap to improve flap survival. Thirty‐two rabbits were randomly divided into DIEP and HNM groups. Untargeted metabolic mechanisms between the DIEP and HNM groups were performed using LC–MS under the filter criteria of fold change >20.0 times or <0.05, and variable importance in projection (VIP) value was set at ≥1, P < 0.05. Between the two groups, flap survival, perfusion, microvasculature, histopathology, and immunohistochemistry of CD31 were assessed on post‐operative day 7. We screened 16 different metabolites that mainly participated in biosynthesis of secondary metabolites, aminoacyl transfer RNA biosynthesis, phenylalanine metabolism, arginine and proline metabolism, among others. The results of the HNM flaps were higher than those of the DIEP flaps ( P < 0.05) in the aspects of flap survival, flap perfusion, and microvasculature. Compared with the DIEP flaps, HNM has a stronger advantage in tissue metabolism. This study provided us with a better understanding and strong evidence in terms of metabolites on how HNM achieves the survival of large multi‐territory perforator flaps.